Learning Organizational Practices and Job Satisfaction: A Case of IT Sector of Karachi - Muhammad Muzammil Ghayas; Malik Muhammad Sheheryar Khan (International Journal of Experiential Learning & Case Studies)
With the increase of globalization and technological advancements since last few decades, organizations have gone through several changes in terms of workplace diversity, learning differentiation as well as organizational culture. This study aims to test the relationship between Learning Organization and Job Satisfaction in the IT Sector of Karachi. Data were collected from 209 such employees of the IT sector who have been working for the same organization for at-least one year. Multiple Regression Analysis was used as the statistical technique. It was found that two of the dimensions of learning organizational practices namely continuous learning and strategic leadership have significant impact on job satisfaction in the IT Sector of Karachi. Hence, it is suggested that managers in the IT Sector of Karachi should design the jobs in such a manner that employees be able to learn continuously. Furthermore, it is suggested that researchers should study the learning organizational practices in relation to other work outcomes such as employee engagement and the turnover intentions.